2016
DOI: 10.5897/jvmah2015.0442
|View full text |Cite
|
Sign up to set email alerts
|

Tick burden and acquisition of immunity to Theileria parva by Tarime cattle in comparison to Sukuma cattle under different tick control regimes in the Lake Zone of Tanzania

Abstract: This study was conducted to determine tick burden and immunological parameters of resistance to East Coast fever (ECF) in Tarime and Sukuma cattle. Tick load, packed cell volume (PCV), Theileria parva (T. parva) specific antibody percent positivity (PP), and prevalence of T. parva parasites were studied in relation to dipping regime, strains, and season. A total of 50 experimental cattle were included in this study. Tick load was determined by whole body counts, antibody percent positivity was determined by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A cohort study done in Tanzania assessed natural tick infestation on Zebu cattle in Tanzania based on geographical locations, animals were dipped once every two to three weeks to control the tick challenge. Results revealed that more animals (P < 0.05) were infested with ticks in Tarime district (96.1 %) than in Serengeti (61.7 %) suggesting that Serengeti Zebu herds exhibited high resistance to ticks than Tarime Zebu herds (Laisser et al, 2016). The Nguni breed of South Africa is one of the most researched Sanga breeds.…”
Section: Tick and Tick-borne Diseases Resistance In Bos Indicus And T...mentioning
confidence: 96%
See 1 more Smart Citation
“…A cohort study done in Tanzania assessed natural tick infestation on Zebu cattle in Tanzania based on geographical locations, animals were dipped once every two to three weeks to control the tick challenge. Results revealed that more animals (P < 0.05) were infested with ticks in Tarime district (96.1 %) than in Serengeti (61.7 %) suggesting that Serengeti Zebu herds exhibited high resistance to ticks than Tarime Zebu herds (Laisser et al, 2016). The Nguni breed of South Africa is one of the most researched Sanga breeds.…”
Section: Tick and Tick-borne Diseases Resistance In Bos Indicus And T...mentioning
confidence: 96%
“…The crosses between Horro (Zebu) and Jersey cattle in Ethiopia have also been reported to exhibit a high degree of tick resistance (Irvin et al, 1996). In another study, acquired immunity against Theileiria parva was demonstrated in two Tanzanian indigenous cattle breeds (Tarime and Sukuma cattle) in the Lake zone (Laisser et al, 2016). In Kenya, Zebu cattle from an East Coast Fever (ECF) endemic area were reported to have a better ability to control the course of the ECF disease and recover in a shorter period than Friesian (B. taurus) cattle (Ndungu et al, 2005).…”
Section: Tick and Tick-borne Diseases Resistance In Bos Indicus And T...mentioning
confidence: 99%